The Construction of “Vulnerability” and “Agency” in Unaccompanied Girls and Adolescents: Perception of the Actors Involved in Chile - Ortiz-López, Juan Eduardo; Poblete-Godoy, Daniela; Acuña Ramirez, Valeria; Dufraix Tapia, Iciar; Salinas Pérez, Sius-Geng; Pavez-Soto, Iskra; Alfaro Contreras, Carmen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
The article examines the perceptions of authorities, professionals, and activists regarding the experiences of unaccompanied girls and adolescent females in Chile, focusing on how intervening adults construct the concepts of vulnerability and agency. Through a qualitative methodology using semi-structured interviews, the study highlights that girls and adolescent females face extreme vulnerability in situations such as pregnancy, sexual exploitation, and other forms of aggression. Despite these challenges, strategies of agency are also identified along their journey, often involving travel with adults in relationships marked by unequal power dynamics. The interviews emphasize the urgency of prioritizing care for pregnant adolescents at border crossings, improving intersectoral coordination to provide comprehensive support, and rethinking public policies and programs from a gender perspective.